2015
DOI: 10.3852/15-027
|View full text |Cite
|
Sign up to set email alerts
|

A survey of genes encoding H2O2-producing GMC oxidoreductases in 10 Polyporales genomes

Abstract: The genomes of three representative Polyporales (Bjerkandera adusta, Phlebia brevispora and a member of the Ganoderma lucidum complex) recently were sequenced to expand our knowledge on the diversity and distribution of genes involved in degradation of plant polymers in this Basidiomycota order, which includes most wood-rotting fungi. Oxidases, including members of the glucose-methanol-choline (GMC) oxidoreductase superfamily, play a central role in the above degradative process because they generate extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 119 publications
4
64
0
1
Order By: Relevance
“…Mutation of R. leguminosarum gmcA did not affect the growth of free-living bacteria but led to decreased antioxidative capacity under the conditions of 5 and 10 mM hydrogen peroxide H 2 O 2 . The direct link between GmcA and H 2 O 2 detoxification has been less reported, while in most wood-rotting fungi, the members of GMC oxidoreductase superfamily play a central role in the degradation process because they generate extracellular H 2 O 2 , acting as the ultimate oxidizer (Ferreira et al, 2015). Our results suggested that cells with GmcA tolerate internally generated or exogenously applied H 2 O 2 .…”
Section: Discussionmentioning
confidence: 64%
“…Mutation of R. leguminosarum gmcA did not affect the growth of free-living bacteria but led to decreased antioxidative capacity under the conditions of 5 and 10 mM hydrogen peroxide H 2 O 2 . The direct link between GmcA and H 2 O 2 detoxification has been less reported, while in most wood-rotting fungi, the members of GMC oxidoreductase superfamily play a central role in the degradation process because they generate extracellular H 2 O 2 , acting as the ultimate oxidizer (Ferreira et al, 2015). Our results suggested that cells with GmcA tolerate internally generated or exogenously applied H 2 O 2 .…”
Section: Discussionmentioning
confidence: 64%
“…For this purpose, fungi secrete H 2 O 2 -generating enzymes, such as glucose oxidases, alcohol oxidases, and aryl-alcohol oxidases (AAOs, EC 1.1.3.7), providing the required H 2 O 2 . They are FAD flavoproteins and belong to the GMC oxidoreductase family within which they are the most abundant members amongst white-rot fungi (Hernández-Ortega et al 2012;Ferreira et al 2015). AAOs produce H 2 O 2 by oxidizing a wide variety of primary aromatic alcohols to aldehydes, such as m-and p-anisyl alcohol, veratryl alcohol, benzyl alcohol, and 5-hydroxymethylfurfural (Guillen et al 1992;Ferreira et al 2005;Feldman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These oxidoreductases are enzymes of CAZy auxiliary activity family 2 (AA2) [8] fungal class-II lignin-modifying peroxidases including lignin peroxidases (LiPs), manganese peroxidases (MnPs), and versatile peroxidases (VPs) that are important in lignin modification [2, 9, 10]. Class-II peroxidases require hydrogen peroxide which may be generated by other CAZy auxiliary activity enzymes belonging to copper radical oxidases (CROs, AA5) and glucose–methanol–choline superfamily (GMCs, AA3) oxidoreductases [11, 12]. Lignin-converting enzyme set also includes the dye-decolorizing peroxidases (DyPs) [10, 13] and laccases.…”
Section: Introductionmentioning
confidence: 99%